Exploring Customary Law: Perspectives of Hazairin and Cornelis Van Vollenhoven and its Relevance to the Future of Islamic Law in Indonesia - Ilham Tohari; Siti Rohmah; Ahmad Qiram As-Suvi (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam)
The difference between Islamic law and Western law in viewing customary law is the core problem that forms the background of this research. This article aims to explore in-depth Customary Law from the perspectives of Hazairin and Cornelis Van Vollenhoven and its relevance to the future existence of Islamic law in Indonesia. This research is a literature study applying a qualitative Juridical-Normative approach. The primary sources for this research are the original works of Hazairin (Tujuh Serangkai tentang Hukum dan Hazairin, Hukum Kewarisan Bilateral Menurut al-Qur’an dan Hadith) and Van Vollenhoven (Het Adatrecht Van Nederlandsch-Indie and its translated version, Van Vollenhoven on Indonesian Adat Law). The secondary sources are all references relevant to the topic of the article. Comparative analysis is used in analyzing the data. The research findings explain that, according to Hazairin, customary law can be applied anywhere as long as it does not contradict Islamic law. In contrast, Van Vollenhoven argues that customary law does not need to consider religion because all humans have equal rights before God, thus rejecting or eliminating customs or traditions is considered undignified. The formation of national law due to culture and tradition is an important part of society. This research provides a conceptual historical-theoretical narrative related to customary law in Indonesia. Despite having different perspectives on customary law, both Hazairin and Van Vollenhoven share the vision that customary law should be made into positive law. Therefore, the existence of customary law needs to be considered by lawmakers to become national positive law.